Analisis Kompetensi Profesional Guru Madrasah Ibtidaiyah dalam Pelajaran Matematika di Purwokerto - Maria Ulpah (Jurnal Penelitian Agama, 2014)
Abstract: Teachers’ professional competence is interesting to study. The datasaid that Indonesian teachers’ professional competence is still low, it’s supportedby score of teachers’ competence test. This study aims to describe elementaryschool teachers’ professional competence in Purwokerto. The professionalcompetence is supported by four indicators. The result of this study shows that theteachers have a high score for mastering mathematics material, a middle score formaking problem relating to daily life, and low score for solving problem with morethan one way and giving reason for steps of solving problem.Keywords: Competence, professional, teacher, mathematics. Abstrak: kompetensi profesional guru menarik untuk dikaji. Data mengatakanbahwa kompetensi profesional guru di Indonesia masih rendah, itu didukung olehskor guru uji kompetensi. Penelitian ini bertujuan untuk menggambarkankompetensi profesional guru sekolah dasar di Purwokerto. Kompetensi profesionaldidukung oleh empat indikator. Hasil penelitian ini menunjukkan bahwa gurumemiliki skor tinggi untuk menguasai materi matematika, nilai tengah untukmembuat masalah yang berkaitan dengan kehidupan sehari-hari, dan skor rendahuntuk memecahkan masalah dengan lebih dari satu cara dan memberikan alasanuntuk langkah-langkah pemecahan masalah.Kata kunci: Kompetensi, profesional, guru, matematika.